Modification of Stiffener Sidewall for 17 m³ Capacity Dump Truck at PT. ABC - Mahandika, Dhidik; La Ode M Firman; Bambang Sulaksono; Erlanda Augupta Pane; Estu Prayogi; Al Diki Akbar Fitrianto (Magister Teknik Mesin Universitas Pancasila, 2025)
ABC operates within the engineering and construction sector, specializing in the service and provision of advanced heavy equipment, including the DV17 type Dump Truck. This Dump Truck model features a loading and unloading body capable of supporting loads of up to several tons. However, there are noted deficiencies in the effectiveness and efficiency of the Sidewall stiffener section, which utilizes 6 supports. A modification was carried out by creating 3 variants or forms of stiffeners. The design method used is the Pahl & Beitz concept design method, with testing performed through static and dynamic simulations using Finite Element Analysis (FEA). Simulation results show that Variant 2 performed the best in both static and dynamic tests, with static simulation values showing stress at 88 MPa, strain at 0.1, displacement at 0.8 mm, a safety factor of 2.9, and a weight of 818.16 kg. The dynamic simulation for Variant 2 recorded stress at 187 MPa, strain at 0.1, displacement at 1.7 mm, and a safety factor of 1.3. When compared to the existing design by PT. ABC, Variant 2 demonstrates superior performance. The current PT. ABC design presents static simulation values of 301 MPa for stress, strain of 0.1, displacement of 4.7 mm, and a safety factor of 0.8. Dynamic simulations reveal a stress value of 411 MPa, strain of 0.1, displacement of 5.1 mm, a safety factor of 0.6, and a weight of 802.63 kg. This indicates that Variant 2 provides optimal performance and a balanced trade-off between safety and stability.